Symptom Assessment among Cancer Patients Receiving Chemotherapy In A Cancer Hospital - Gautam, Roshani; Kalikotey, Bhagwati; Shrestha, Krishna Devi; Shrestha, Archana (Tribhuvan University Journal, 2022)
People with cancer usually experience various distressing symptoms while receiving chemotherapy. Early identification of distressing symptoms of patients receiving treatment is a crucial step toward providing quality nursing care for patients. This study aimed to assess the frequency, severity and distressing symptoms and its predictors among cancer patients who are receiving chemotherapy. An Analytical cross-sectional study was done among 233 people receiving cancer chemotherapy in a Cancer Hospital. Convenience sampling method was adopted to select sample and data was collected by in-person interview. Out of 233 respondents, less than half(42.6%) belonged to the 40-59 years age group and male (53.6%). The common physical symptoms were pain (70%), lack of energy (67.8%), nausea (58.8%) and psychological symptoms were feeling sad (43.8%), worrying (43.8%) and difficulty sleeping (18.5%). The most severe symptoms experienced by respondents were pain, dry mouth, lack of energy and shortness of breath. Patient’s age (β=0.321, p